DYNAMIC STABILITY ANALYSIS OF A DIESL-HYDRAULIC LOCOMOTIVE ON TANGENT AND CURVE TRACKS - NURFEBRIARTANTO (NIM : 13107119); Pembimbing Dr. Ir Andi Isra Mahyuddin, ADITYA
Indonesia, with a large population, needs a reliable transportation system to serve the mobility of its people. Rail transportation could answer the need for challenges faced by the country in providing dependable mass transportation system. Hence, the development of rail-vehicle and rail transportation system should become a priority. To that end, a Diesel-Hydraulic Locomotive is designed and will be manufactured. In the development stage of a rail vehicle, analyses to evaluate its dynamic stability are required. In this work, the Diesel-Hydraulic Locomotive is modeled as a multibody system consisting of several rigid bodies interconnected by elastic elements. Multibody dynamic analysis of the system is performed to obtain the dynamic response and stability evaluation. Stability on tangent and curve tracks as well as the Locomotive dynamic response is investigated. The stability on tangent track is limited by the locomotive critical speed, Vcr, evaluated for various wheel conicity and primary suspension stiffness. Operation beyond this critical speed will result in hunting which could lead to derailment. Stability evaluation on the curve track is conducted through simulation of the model negotiating a curve with rail irregularity for various radii. The maximum and minimum velocities for negotiating the curve are evaluated. To evaluate the derailment safety on the curve track, the wheel-rail contact force ratio in lateral and vertical directions (L/V), and the loading-unloading ratio of the primary suspension in the vertical direction are computed, and are compared to limiting criteria. The results are found to meet the safety criteria. The guiding lateral force on the wheel entering a curve track for various primary suspension stiffnesses is also evaluated because its effect on wear rate of the wheel and rail. While lower stiffness value of the primary suspension results in favorable L/V and lower guiding force, it yields lower critical speed on tangent track. Hence, a parametric study of the primary suspension stiffness is conducted to obtain optimum value which yield acceptable critical speed and guiding force, yet still meet the safety criteria.